The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.14260/jemds/2014/3155
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Menisci of the Knee Joint in Population of East Godavari Region of Andhra Pradesh

Abstract: ABSTRACT:The morphometrical data related to the menisci of the adults have been reported by few authors but data specific to the population of East Goadavari region have not been reported. The aims of the present study were to analyse the external circumference thickness, the width, peripheral and inner border lengths, and the distance between anterior and posterior horns of the menisci and to compare them with those which are available in the literature. The menisci from 100 knee joints of the formalin fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 13 publications
4
6
2
Order By: Relevance
“…Comparing the mean outer circumference of the medial and lateral menisci in the present work, the medial meniscus exhibited larger values than that of the lateral which was statistically significant. This finding is concordant with the results provided by Braz and Silva [16] , Murlimanju et al, [6] , Ashwini et al, [5] and Rao et al, [17] . This finding could be explained be the fact that the medial tibial condyle is larger than the lateral.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Comparing the mean outer circumference of the medial and lateral menisci in the present work, the medial meniscus exhibited larger values than that of the lateral which was statistically significant. This finding is concordant with the results provided by Braz and Silva [16] , Murlimanju et al, [6] , Ashwini et al, [5] and Rao et al, [17] . This finding could be explained be the fact that the medial tibial condyle is larger than the lateral.…”
Section: Discussionsupporting
confidence: 94%
“…The present cadaveric study is in agreement with Rao et al, [17] who concluded that the measurements of width of anterior and middle 1/3 of lateral meniscus were much higher than those of medial meniscus which is statistically significant, while the posterior 1/3 of medial meniscus was wider than the lateral but it was statistically nonsignificant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For calculating thickness of menisci researchers have used different methods and techniques in cadavers and living subjects. The common technique used was digital Vernier caliper to calculate the thickness of menisci that is measured with the help of a non-elastic cotton thread at three different levels as anterior, middle and posterior (1,2,5,6) . Dhanajaya et al…”
Section: Thickness Of Meniscimentioning
confidence: 99%